Persistent Occurrence of Strip‐Like Plasma Density Bulges at Conjugate Lower‐Mid Latitudes During the September 8–9, 2017 Geomagnetic Storm. Issue 5 (7th May 2021) - Wan, Xin; Zhong, Jiahao; Xiong, Chao; Wang, Hui; Liu, Yiwen; Li, Qiaoling; Kuai, Jiawei; Weng, Libin; Cui, Jun
Abstract: During the geomagnetic storm on September 8–9, 2017, shoulder‐like structures were persistently captured in the lower‐mid latitudes at multiple local times, by Swarm and DMSP satellite observations. A more telling terminology of such shoulder‐like structure called strip‐like bulge is proposed in this study, due to its global presence that spanning over 150° in longitude but only over 1°–5° in latitude. The strip‐like bulges can be categorized into sharp and blunt types depending on the sharpness of the density peaks. The blunt type was short‐lived and appeared earlier than the sharp type in the afternoon‐sunset sector. The sharp type was long‐lived and appeared at all the observed local times. Both two types of strip‐like bulges were dominated by the ion composition of the H + / He +, rather than O + . This is the first evidence that the plasmaspheric particles are involved in forming the ionospheric structure at such low latitude. Moreover, the equatorward movement of the bulges shared the same trends with the earthward movement of the plasmapause. These two types of strip‐like bulges showed different longitudinal dependencies controlled by the magnetic declination. We suggest that the combined effects from the plasmaspheric downwelling and disturbance neutral wind were responsible for the appearance of the strip‐like bulges. Plain Language Summary: In the lower‐mid latitude ionosphere, shoulder‐like plasma density structures are occasionally snapshotted by satellite passes or regional TEC maps during geomagnetic storms. Such ionospheric structures can cause positioning errors for GNSS applications. Previous fragmentary investigations recognize shoulder‐like structures mainly as a regional phenomenon. This study portrays a new global picture of a shoulder‐like structure and finds it more suitable to be termed as strip‐like bulges. The zonal extent of the bulge is beyond 150° in longitude. Some distinctive occurrence features are further revealed, implying the combined formation mechanisms involving plasmaspheric downwelling and disturbed neutral winds. Key Points: Strip‐like plasma density bulges with wide zonal extent exist in lower‐mid latitudes ionosphere during the storm investigated Dominance of H + / He + indicates that plasmaspheric particles were involved in forming the bulges at such low latitude Distinctive longitudinal dependences of the bulges on the magnetic declination suggest the effects of neutral winds